MANAGEMENT OF AUTOMATIC AND CONVENTIONAL SPRAYING TECHNIQUES IN GREENHOUSES, A COMPARATIVE STUDY - Hayder, H. Luaibi; Nawal, A. Omran; Firas Salim Al-Aani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to used automated spraying inside greenhouses using automated sprayers and compare it with traditional spraying. An experiment was conducted in one of the greenhouses at the Research Center of the College of Agricultural Engineering Sciences, University of Baghdad / Jadriyah, during the summer season on the cucumber crop cultivar CADIAR F1. The techniques used in the spraying process included a locally-made automated sprayer to spray pesticides inside the greenhouses horizontally and a knapsack sprayer. Two types of nozzles were used: universal flat fan nozzle (120-02C) and (120-04C), with three different pressures (1.8, 3, 5) bar, using a constant speed of 2 km h-1. This was to study the spray quality characteristics and the amount of waste resulting from using both methods. The experiment results indicated the automated sprayers’ success in achieving good spray quality with less waste compared to the backpack sprayer. The automated sprayer achieved good results in increasing the spray penetration rate into the foliage and reducing the waste rate of pesticides by (34.3%) and (2.42%) respectively, compared to the backpack sprayer, which achieved (14.46%) and (18.42%) respectively.